Length of Stay Increases 90-day Readmission Rates in Patients Undergoing Primary Total Joint Arthroplasty. (16th March 2022) - Benito, Jorge; Stafford, Justin; Judd, Hyrum; Ng, Mitchell; Corces, Arturo; Roche, Martin W.
Abstract : Background: Postoperative length of stay (LOS) of 1 day compared with that of 2 to 4 days after primary total knee arthroplasty (TKA) or total hip arthroplasty (THA) and 90-day readmissions. Methods: PearlDiver identified TKA (n = 648, 758) and THA patients (n = 346, 732) between 2005 and 2014. Groups consisted of control (LOS = 1 day) and study (LOS = 2 to 4 days) groups. Study and control groups were matched to age, sex, and Elixhauser Comorbidity Index. Logistic regression analysis and odds ratio analyzed 90-day readmission rates. P < 0.05 was statistically significant. Results: TKA patients' LOS of 2 days (odds ratio [OR], 2.89; 95% confidence interval [CI], 2.77 to 3.00), LOS of 3 days (OR, 2.80; 95% CI, 2.69 to 2.91), and LOS of 4 days (OR, 2.83; 95% CI, 2.72 to 2.95) had greater 90-day readmission compared with LOS of 1 day ( P < 0.05). THA patients with an LOS of 2 days (OR, 2.93; 95% CI, 2.77 to 3.10), an LOS of 3 days (OR, 2.91; 95% CI, 2.75 to 3.07), or an LOS of 4 days (OR, 2.91; 95% CI, 2.73 to 3.05) had greater 90-day readmission compared with an LOS of 1 day ( P < 0.05). Conclusion: LOS >1 day has greater odds of 90-day readmission after an index procedure. Efficient progression to early discharge regarding patient-specific risk factors plays a large role in preventing readmission.